Antiphospholipid antibody tests: spreading the net. Issue 11 (7th April 2005) - Bertolaccini, M L; Gomez, S; Pareja, J F P; Theodoridou, A; Sanna, G; Hughes, G R V; Khamashta, M A
Abstract : Objective: To examine the hypothesis that testing for new antiphospholipid antibody specificities may help to identify the antiphospholipid syndrome (APS) in patients with systemic lupus erythematosus (SLE) with thrombosis who are repeatedly negative for anticardiolipin antibodies (aCL) and/or lupus anticoagulant (LA). Methods: Three groups of patients with SLE were studied: ( a ) SLE/APS (n = 56): 51 female, mean (SD) age 46 (11) years, fulfilling 1999 Sapporo criteria for the APS; ( b ) SLE/thrombosis (n = 56): 53 female, age 42.6 (12) years, all with a history of thrombosis and persistently negative for aCL and/or LA; ( c ) SLE only (n = 56): 53 female, age 40 (11) years, without a history of thrombotic events. aCL and LA were retested in all samples. All patients were tested for anti-β2 -glycoprotein I (anti-β2 GPI) and antiprothrombin antibodies (aPT) by coating prothrombin on irradiated plates or using phosphatidylserine-prothrombin complex as the antigen (aPS-PT). Results: Anti-β2 GPI were only present in patients from the SLE/APS group, all of whom were also positive for aCL. aPT and aPS-PT were also more commonly found in SLE/APS than in SLE/thrombosis or SLE only groups (54% v 5%, p<0.0001 or v 16%, p<0.0001 for aPT and 63% v 2%, p<0.0001 or v 11%, p<0.0001 for aPS-PT, respectively). No differences were found between SLE/thrombosis and SLE only groups (p = 1.5 for β2 GPI, p = 0.1 for aPT, and p = 0.1 for aPS-PT). Conclusion: Testing for aPT in patients with SLE with thrombosis, but persistently negative for aCL and LA, may be helpful in some selected cases. Anti-β2 GPI are not present in patients who are negative for aCL.